2009
DOI: 10.1371/journal.ppat.1000546
|View full text |Cite|
|
Sign up to set email alerts
|

Essential Role of Cyclophilin A for Hepatitis C Virus Replication and Virus Production and Possible Link to Polyprotein Cleavage Kinetics

Abstract: Viruses are obligate intracellular parasites and therefore their replication completely depends on host cell factors. In case of the hepatitis C virus (HCV), a positive-strand RNA virus that in the majority of infections establishes persistence, cyclophilins are considered to play an important role in RNA replication. Subsequent to the observation that cyclosporines, known to sequester cyclophilins by direct binding, profoundly block HCV replication in cultured human hepatoma cells, conflicting results were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
278
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 245 publications
(289 citation statements)
references
References 57 publications
10
278
1
Order By: Relevance
“…Val and Iso) at the P3 and P4 positions (supplemental Fig. 2), consistent with what has also been observed at the NS5A5B boundary (31). From both the luciferase and colony-forming assays, we concluded that the P433 VV mutation, which gives rapid cleavage of the NS4B5A boundary, severely impairs replication.…”
Section: Resultssupporting
confidence: 86%
“…Val and Iso) at the P3 and P4 positions (supplemental Fig. 2), consistent with what has also been observed at the NS5A5B boundary (31). From both the luciferase and colony-forming assays, we concluded that the P433 VV mutation, which gives rapid cleavage of the NS4B5A boundary, severely impairs replication.…”
Section: Resultssupporting
confidence: 86%
“…The power of this method is illustrated by NS5A and CypA. These two proteins are involved in HCV assembly (57,58); they cosediment with virions in density gradients (Figs. 1A and 2E), but they are not detectable in virus fractions after affinity purification (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, NS5A is of particular interest because it is the target of efficient direct acting antivirals (e.g. daclatasvir) (7) and its interaction with the human cyclophilin A (CypA), an essential peptidylprolyl cis-trans isomerase (PPIase) (8,9), is also targeted by the most advanced host-targeted antiviral (alisporivir) (10,11).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%